1995
DOI: 10.1111/j.1464-410x.1995.tb07411.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma metastases to the skin: a not so rare case?

Abstract: Metastases to the skin from a renal cell carcinoma as first evidence of the disease may not be as rare as the literature describes. Definite proof of the origin of the tumour requires specialized immunohistochemical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 8 publications
1
27
0
2
Order By: Relevance
“…In recent times, a few case reports have appeared in the literature describing the rarity of presentation and the need for a high index of suspicion in evaluating a patient presenting with a skin tumor [1][2][3][4][5]]. Recently, Kouroupakis et al [6] have suggested that such patients usually present with synchronous skin metastasis rather than metachronous metastasis. We reviewed our experience with 306 cases of renal cell carcinoma (RCC) treated at our center over the last 12 years in order to determine the incidence and implications of cutaneous metastasis from RCC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, a few case reports have appeared in the literature describing the rarity of presentation and the need for a high index of suspicion in evaluating a patient presenting with a skin tumor [1][2][3][4][5]]. Recently, Kouroupakis et al [6] have suggested that such patients usually present with synchronous skin metastasis rather than metachronous metastasis. We reviewed our experience with 306 cases of renal cell carcinoma (RCC) treated at our center over the last 12 years in order to determine the incidence and implications of cutaneous metastasis from RCC.…”
Section: Introductionmentioning
confidence: 99%
“…When renal cancer has already produced metastases, its prognosis is poor, because it can be cured with neither radiation therapy, nor traditional antineoplastic drugs (chemotherapy), nor hormones. 4,8 Our patient died without undergoing specific treatment for renal tumor.…”
Section: Discussionmentioning
confidence: 91%
“…A small epidermal invagination delimits the lesion from the normal dermis. 8 Some protein antigens are evidenced by use of immunohistochemistry, such as the epithelial membrane antigen (EMA), vimentin, keratin, and carcinoembryonic antigen (CEA). The positive results with vimentin, EMA, and keratin are high-probability indicators of renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous metastases from RCC are frequently present in patients with previous history of such malignancy, being exceptional the reported cases in which skin affection was first clinical manifestation [5]. Cutaneous metastases from RCC are usually located in head however that can be found in thorax and upper limbs; most of them are unique described as a rapid growing tumor, red-bluish, lobulated, of well defined edges, ulcerated at times [6].…”
Section: Cutaneous Metastases and Right Hemiplegia As First Manifestamentioning
confidence: 99%